2018
DOI: 10.3390/brainsci8050085
|View full text |Cite
|
Sign up to set email alerts
|

Language Experience Changes Audiovisual Perception

Abstract: Can experience change perception? Here, we examine whether language experience shapes the way individuals process auditory and visual information. We used the McGurk effect—the discovery that when people hear a speech sound (e.g., “ba”) and see a conflicting lip movement (e.g., “ga”), they recognize it as a completely new sound (e.g., “da”). This finding that the brain fuses input across auditory and visual modalities demonstrates that what we hear is profoundly influenced by what we see. We find that cross-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 60 publications
0
26
2
Order By: Relevance
“…Moving beyond lexical considerations alone, it could be the case that bilingualism hones low‐level cross‐modal exchanges between the auditory and visual modality. This is supported by brain imagery evidence showing that bilingual children (Della Rosa et al., 2013) and adults (Li, Legault, & Litcofsky, 2014) have more gray matter density and cortical thickness in two multisensory pathways that are highly engaged in audio–visual speech processing and are more inclined to bind auditory and visual features of speech (McGurk illusion, Marian, Hayakawa, Lam, & Schroeder, 2018) and non‐speech events (Double flash illusion, Bidelman & Heath, 2019. Sound‐color synesthesia, Ward, 2013; Watson et al., 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Moving beyond lexical considerations alone, it could be the case that bilingualism hones low‐level cross‐modal exchanges between the auditory and visual modality. This is supported by brain imagery evidence showing that bilingual children (Della Rosa et al., 2013) and adults (Li, Legault, & Litcofsky, 2014) have more gray matter density and cortical thickness in two multisensory pathways that are highly engaged in audio–visual speech processing and are more inclined to bind auditory and visual features of speech (McGurk illusion, Marian, Hayakawa, Lam, & Schroeder, 2018) and non‐speech events (Double flash illusion, Bidelman & Heath, 2019. Sound‐color synesthesia, Ward, 2013; Watson et al., 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Bilingual adolescents and adults also show different patterns of speech perception and encoding, even for low-level information such as the fundamental frequency of speech syllables (Krizman, Marian, Shook, Skoe, & Kraus, 2012). Integration of auditory and visual information is affected by bilingualism: bilinguals are less susceptible to illusions that fuse asynchronous nonlinguistic auditory and visual stimuli into a single percept (Bidelman & Heath, 2018), but are more susceptible to such illusions with mismatching audiovisual speech syllables (Marian, Hayakawa, Lam, & Schroeder, 2018). There are also effects of linguistic and cultural immersion for how adults perceive and process color, even in pre-attentive tasks (Athanasopoulos, Dering, Wiggett, Kuipers, & Thierry, 2010), as well as for how speakers of different languages process the visual world and perform in visual search tasks (Chabal, Schroder, & Marian, 2015).…”
Section: Perceptionmentioning
confidence: 99%
“…Since past research has shown differences in language processing between balanced and unbalanced bilinguals (e.g., Rosselli et al, 2016), it was important to recruit a sample with balanced bilinguals for the present study. Therefore, bilinguals' language abilities were evaluated using self-report data from the Language Experience and Proficiency Questionnaire (LEAP-Q; Marian et al, 2007). This scale asked them to rate their understanding of their languages, as well as their speaking and reading skills in both languages, on a scale from 0 to 10.…”
Section: Participant Selection Proceduresmentioning
confidence: 99%